2010
DOI: 10.1080/03079457.2010.518314
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale survey ofCryptosporidiumspp. in chickens and Pekin ducks (Anas platyrhynchos) in Henan, China: prevalence and molecular characterization

Abstract: Few data are available on the molecular characterization of Cryptosporidium spp. in chickens and ducks in China. In this study, 2579 faecal samples from 46 chicken farms and eight Pekin duck farms in 21 prefectures in Henan Province were examined. The overall infection rate of Cryptosporidium was 10.6% (163/1542) in layer chickens (10 out of 17 farms), 3.4% (16/473) in broilers (five out of 29 farms), and 16.3% (92/564) in Pekin ducks (four out of eight farms), respectively. The highest infection rates were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 47 publications
6
39
5
1
Order By: Relevance
“…Thus far, there are few data available about the infection rate of Cryptosporidium in poultry, especially in chickens in China. It was reported that the infection rate of Cryptosporidium was 3.4% in Henan and 23.8% in Shandong, China [26, 27]. Moreover, the rate was 3.75% in the Garmsar region, Iran, and 4.5% in Tunisia [21, 24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, there are few data available about the infection rate of Cryptosporidium in poultry, especially in chickens in China. It was reported that the infection rate of Cryptosporidium was 3.4% in Henan and 23.8% in Shandong, China [26, 27]. Moreover, the rate was 3.75% in the Garmsar region, Iran, and 4.5% in Tunisia [21, 24].…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, the prevalence of Cryptosporidium spp. has been reported in detail in quails, chickens, Pekin ducks, pet birds, and ostriches in Henan, and most species have been identified as C. baileyi and C. meleagridis [18, 2729]. The epidemiological investigation of Cryptosporidium in poultry in Zhejiang Province was carried out in our research.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from C. baileyi obtained from a chicken [23], provided by Prof. Longxian Zhang of Henan Agricultural University, was used as a positive control, and deionized water was used as a negative control. All nested PCR products were visualized by electrophoresis in 2% agarose gel stained with ethidium bromide before sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In Algeria, a report showed a high prevalence of C. meleagridis: 34% (26/90) in chickens and 44% (25/57) in turkeys (BAROUDI et al, 2013). However, in China, a low prevalence was described for C. meleagridis among broiler chickens (0.52%; 2/385) (WANG et al, 2014b), laying hens (0.19%; 3/1542) (WANG et al, 2010) and quails (0.22%; 4/1818) . Li et al (2012) found C. meleagridis in 24.4% (22/90) of the wastewater samples collected from four cities in China.…”
Section: Importance For Public Healthmentioning
confidence: 99%